Redefining treatment paradigms: Early use of dapagliflozin and empagliflozin in acute heart failure – a systematic review and meta-analysis of randomized controlled trials - Immanuel, Surya S.; Yonatan, Eric R.; Tandecxi, Gabriel; Anthony, Clifford P.; Chan, Janice Z.; Sunardi, Andrew EP.; Posangi, Ira; Bandana, Victor (Narra Sains Indonesia, 2025)
Sodium-glucose co-transporter 2 inhibitors (SGLT2i) have proven to significantly reduce mortality and rehospitalization in heart failure with reduced ejection fraction (HFrEF). Supported by the 2023 European Society of Cardiology (ESC) guidelines and the safety, tolerability, and efficacy of rapid optimization of heart failure (STRONG-HF) trial, SGLT2i offer improved outcomes with a favorable safety profile, emphasizing their pivotal role in HFrEF management. The aim of this study was to evaluate early initiation with dapagliflozin and empagliflozin, focusing on their efficacy and safety in acute heart failure (AHF). Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we searched seven databases for randomized controlled trials on SGLT2i in AHF (2019–2024). Outcomes included all-cause mortality, heart failure (HF)-related events, all-cause rehospitalization, length of hospital stay, diuretic response, serum electrolytes, and adverse events (AEs). The Cochrane Risk of Bias 2 tool was used. Data were analyzed using a random-effects model and presented as standardized mean differences and risk ratios with 95% confidence intervals. A subgroup analysis was conducted based on intervention. Nine studies encompassing 1,417 patients with a generally low risk of bias were included. Initiating SGLT2i within five days of admission significantly reduced in-hospital all-cause mortality risk by 42% and in-hospital worsening HF during rehospitalization by 39%. SGLT2i also significantly reduced serious AEs risk by 27%. No significant differences were found in other outcomes, including specific AEs (acute kidney injury, hepatic injury, symptomatic hypotension, hypoglycemia, urinary tract infections, and diabetic ketoacidosis). The analysis showed homogeneity, with no significant differences between SGLT2i. The study highlights that initiating SGLT2i within five days of admission significantly reduces all-cause mortality and worsening HF during rehospitalization, with a better safety profile than placebo.